Substance Use: Teen Talk Among Early Adolescence - Aparnavi P; Jeevithan Shanmugam; Ramesh Rathinamoorthy; Nalina B; Dhakshana P (Medsci Publications, 2023)
A teen talk session for middle school children to speak on substance use was organised with a moderator to guide the discussion points under each section and ensure participation of all the children. From the talking points it was understood that children in the age group of 11 to 14 years also use substance like Coolip, Bidi and Hans. Children spend their evenings unsupervised and hanging out with friends using substance. Hence, they become more vulnerable to substance use.  Students were requesting for an enabling environment to constructively use their time. Thus regular activities should be conducted at school level for the prevention of substance use.